Carbon‐Quantum‐Dot‐Derived Nanostructured MnO2 and Its Symmetrical Supercapacitor Performances. Issue 30 (9th August 2018) - Prasath, Arul; Athika, Mattath; Duraisamy, Ezhumalai; Sharma, Arumugam Selva; Elumalai, Perumal
Abstract: We report here synthesis of nanostructured MnO2 by using carbon‐quantum dot (CQD) as reducing agent which is obtained by environmentally benign approach from waste material. The obtained carbon quantum dot‐MnO2 nanohybrid is characterized by various analytical techniques. The spectral studies reveal the characteristic absorption/emission features of nanostructured CQD‐MnO2 . The X‐ray‐diffraction and microscopic analysis indicate that the synthesized CQD‐MnO2 is crystalline in nature with the grain size in the range of 250 − 300 nm. Electrochemical studies reveals that the carbon quantum dot‐MnO2 nanohybrid electrode exhibits a high specific capacitance of 189 F g ‐1 at 0.14 A g ‐1 with an excellent stability over 1200 charge‐discharge cycles. The excellent electrochemical performance is attributed to the large surface area and high conductivity due to the presence of conductive nanonetwork of the CQD in the carbon quantum dot‐MnO2 matrix. The symmetric supercapacitor (CQD‐MnO2 |Na2 SO4 |CQD‐MnO2 ) constructed using the carbon quantum dot‐MnO2 electrodes delivers high energy and power densities with a wide operating potential window of 0 ‐ 1.6 V. Abstract : Nanostructured MnO2 was generated by a simple one‐step process using waste milk‐derived carbon quantum dot. The CQD‐MnO2 nanohybrid exhibited high specific capacity of 189 F g −1 . The symmetric supercapacitor delivered high energy density of 62 Wh kg −1 at power density of 3385 W kg −1 with wide voltage window of 0–1.6 V.